Effect of Workplace Diversity and Inclusion on Institutional Performance in Selected Public Higher Education Institutions in the Gambia - Jebou, Mohammed; Badjie, Gibriel (Universitas Nusantara PGRI Kediri, 2025)
Research aim: This study aimed to examine the effect of workplace diversity and inclusion on the performance of public higher education institutions in The Gambia. Design/Methode/Approach: A correlational research design was employed, using quantitative methods to collect data. Structural equation model (SEM) was adopted in addressing the hypothesis using Smart PLS. The study has 92.4% response rate. Research Finding: In general, the findings indicate that Workplace Diversity and Inclusion has a positive effect on the performance of Public Higher Education Institutions in The Gambia. Likewise, the result of the study also indicates that Workplace Inclusion and Organizational Culture were found to have positive effects on Organizational Performance, while Workplace Diversity was also observed to have a positive influence on Organizational Culture. However, it was discovered that there is a negative relationship between Workplace Inclusion and Organizational Culture. Practitionel/Policy implication: The study underscores the importance of prioritizing Workplace Diversity and Inclusion management for senior executives in public higher education institutions thus, emphasizes the need for clear communication channels to align diversity and inclusion management objectives with institutional goals.